The reinforcing value of food and non-food alternative: Associations with BMI z-score and percent fat mass. (August 2019) - Wong, Samantha; Kong, Kai Ling; Buchholz, Andrea C.; Haines, Jess
Abstract: There is growing evidence of an association between the relative reinforcing value of food (RRVF; how hard a child is willing to work for a food versus a non-food reinforcer) and weight across many life stages, but few studies have examined this association among preschool age children. This study investigated the association between the RRVF (measured as the food reinforcing ratio (FRR)) and body mass index (BMI) z-score and percent fat mass (%FM), in 3 year-old children. The sample was comprised of 33 children who were 3 years of age (36–47 months). Children selected their favourite food reinforcer (cookie) and non-food (audiobook) reinforcer to be used in the FRR task, which was delivered using a sequential progressive fixed ratio reward schedule. Child height, weight and percent body fat using bioelectrical impedance analysis were assessed by trained research staff. Linear regression analyses showed that FRR was significantly and positively associated with BMI z-scores. FRR was not significantly associated with %FM. Findings from this study support the RRVF as a potential risk factor in the development of childhood obesity. Longitudinal research involving larger sample sizes would strengthen future research exploring associations between RRVF and body composition in preschool age children. Highlights: Food Reinforcing Ratio (FRR) was significantly and positively associated with BMI z-scores among 3 year-old children This study builds on existing research by using a food vs. non-food design and a sequential fixed ratio schedule protocol.